Enter a problem...
Algebra Examples
2x-3y=6
Step 1
Step 1.1
The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.
y=mx+b
Step 1.2
Subtract 2x from both sides of the equation.
-3y=6-2x
Step 1.3
Divide each term in -3y=6-2x by -3 and simplify.
Step 1.3.1
Divide each term in -3y=6-2x by -3.
-3y-3=6-3+-2x-3
Step 1.3.2
Simplify the left side.
Step 1.3.2.1
Cancel the common factor of -3.
Step 1.3.2.1.1
Cancel the common factor.
-3y-3=6-3+-2x-3
Step 1.3.2.1.2
Divide y by 1.
y=6-3+-2x-3
y=6-3+-2x-3
y=6-3+-2x-3
Step 1.3.3
Simplify the right side.
Step 1.3.3.1
Simplify each term.
Step 1.3.3.1.1
Divide 6 by -3.
y=-2+-2x-3
Step 1.3.3.1.2
Dividing two negative values results in a positive value.
y=-2+2x3
y=-2+2x3
y=-2+2x3
y=-2+2x3
Step 1.4
Write in y=mx+b form.
Step 1.4.1
Reorder -2 and 2x3.
y=2x3-2
Step 1.4.2
Reorder terms.
y=23x-2
y=23x-2
y=23x-2
Step 2
Using the slope-intercept form, the slope is 23.
m=23
Step 3
